Persepsi Perawat Terhadap Kegunaan Dan Kemudahan EMR Untuk Pengisian Pengkajian Pada Pasien Kritis: Pilot Study - Prawira, Ricky; Saputra, Dikki (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The implementation of Electronic Medical Records (EMRs) in the initial assessment of critically ill patients is a key innovation to enhance the efficiency and accuracy of nursing documentation This study is a pilot study that aims to determine nurses’ perceptions of the usefulness and ease of use of EMR in the initial assessment process for critical patients. A total of 20 nurses from intensive care units in a private hospital in Palembang participated using a total sampling technique. The instrument used was a questionnaire based on the Technology Acceptance Model (TAM). The results showed an average perception score of 4.31 for usefulness and 4.32 for ease of use, both categorized as technology very acceptance. The highest-rated usefulness indicator was “speeds up work” (4.49), while the highest ease-of-use indicator was “easy to control” (4.48). These positive perceptions were influenced by respondent characteristics predominantly female, young (ages 25–30), diploma-level education (D3), and over two years of work experience. The findings indicate that EMRs are well accepted by nurses, especially when supported by user-friendly design and adequate training. This study provides a valuable foundation for the further development and optimal implementation of EMRs in critical care environments.